Radical excision of inguinal condyloma acuminatum following 51 years of untreated growth, found to be squamous cell carcinoma - Asher Mandel (Elsevier, 2022)
Giant condyloma acuminatum, caused by herpes simplex virus infection, is a large cauliflower shaped lesion that has a propensity to infiltrate surrounding tissues with paradoxically benign microscopic/histological appearance. This lesion is often benign, though it does have the potential for malignant transformation. Here we present a case that demonstrates this potential and describes the pathological and histological findings in detail. The report concludes with the clinical reasoning for considering surgical resection in these patients.